Land use intensity indirectly affects ecosystem services mainly through plant functional identity in a temperate forest - Chillo, María Verónica (2018)
Land‐use change is known to affect biodiversity, and there is increasing concern regarding how these changes may impact the provision of ecosystem services. Although functional composition (diversity and identity) could influence ecosystem properties and services at the community level, there is little quantitative understanding of these relationships in the field. Here, we evaluate the direct and indirect effects (through ecosystem properties) of biodiversity on the provision of multiple ecosystem services in native mixed forest in north‐west Patagonia, and how land‐use intensity influences these relationships. We used structural equation modelling to test hypotheses regarding the relationship between understorey plant functional composition, two ecosystem properties, four ecosystem services and silvopastoral use intensity (SUI). We also evaluated two alternative models to assess the mechanism behind biodiversity and ecosystem properties relationships (biomass ratio and niche complementarity). Finally, we performed pairwise correlations to identify synergies and trade‐offs between ecosystem services. SUI affected functional composition, and the provision of three out of four ecosystem services was indirectly affected by land‐use intensity through changes in ecosystem properties. We found that this indirect effect of biodiversity on ecosystem services happens mainly through changes in functional identity rather than functional diversity. Under increasing land‐use intensity, functional composition changed towards a community characterized by a resource acquisition strategy. Trade‐offs between ecosystem services (provisioning vs. regulating) were enhanced under high SUI, while synergies where enhanced under low SUI (provisioning vs. cultural). Thus, although the strength of these relationships varied between SUI, its nature (trade‐off or synergy) stayed the same. Our results expand on previous studies by simultaneously considering the effect of land‐use intensification directly on functional composition and on the ecosystem processes underpinning ecosystem services, as well as on the relationship among them. We provide evidence of an indirect effect of land‐use intensification on multiple ecosystem services through biodiversity. Moreover, we found that functional identity is more important than diversity for ecosystem functionality. Land‐use intensification affects biodiversity, and thus, ecosystem properties, but does not change the relationship among ecosystem services.